DC conductivity and AC impedance of Mn doped magnesia alumina spinel (MgAl2-2xMn2xO4) over a large temperature range. Issue 4 (April 2019) - Jia, Hongyao; Zhou, Wancheng; Duan, Shichang; Nan, Hanyi; Luo, Fa; Zhu, Dongmei
Abstract: MgAl2-2x Mn2x O4 (MAMO) with x = 0-0.12 was synthesized in a single-phase form by solid-state reaction. XRD analysis showed that the samples had the cubic center structure of the Fd-3 m space group. Electrical properties of the samples were studied over the temperature range of 300 K∼1073 K. The results showed that the DC conductivity (σDC ) increased from 10 −11 S/cm at 300 K (MAMO, x = 0) to 10 -3 S/cm at 1073 K (MAMO, x = 0.12). The equivalent circuit of the complex impedance spectra suggested that the relaxation of charge carriers was of non-Debye type. The conduction was mainly caused by grain boundaries and the capacitance was mainly attributed to polarization. The complex permittivity values ( ε' and ε'') were increased by two orders of magnitude with the increase in Mn content and temperature over the measured frequency range (1 Hz-1 MHz). Therefore, doping with Mn could be applied to modify the electrical properties of MAMO at high temperature.